In Vivo HOXB7 Gene Silencing and Cotreatment with Tamoxifen for Luminal A Breast Cancer Therapy - Ana Beatriz Caribé dos Santos Valle; Fábio Fernando Alves da Silva; Maria Ângela Pepe Carneiro; Bruno Espuche; Guilherme Diniz Tavares; Emerson Soares Bernardes; Sergio Enrique Moya; Frederico Pittella (MDPI AG, 2024)
Background: Acquired resistance and adverse effects are some of the challenges faced by thousands of Luminal A breast cancer patients under tamoxifen (TMX) treatment. Some authors associate the overexpression of HOXB7 with TMX resistance in this molecular subtype, and the knockdown of this gene could be an effective strategy to regain TMX sensitivity. Therefore, we used calcium phosphate hybrid nanoparticles (HNP) for the delivery of short interfering RNA molecule (siRNA) complementary to the HOXB7 gene and evaluated the RNA interference (RNAi) effects associated with TMX treatment in breast cancer in vivo. Methods: HNP were prepared by the self-assembly of a methoxy-poly (ethylene glycol)-block-poly (L-glutamic acid) copolymer (PEG-pGlu) and the coprecipitation of CaPO4 to incorporate siRNA. The in vitro cell viability and migration were evaluated prior to in vivo experiments. Further, animals bearing early-stage and advanced Luminal A breast cancer were treated with HNP-siHOXB7, HNP-siHOXB7 + TMX, and TMX. Antitumoral activity and gene expression were evaluated following histopathological, hematological, and biochemical analysis. Results: The HNP were efficient in delivering the siRNA in vitro and in vivo, whilst HOXB7 silencing associated with TMX administration promoted controlled tumor growth, as well as a higher survival rate and reduction in immuno- and hepatotoxicity. Conclusions: Therefore, our findings suggest that HOXB7 can be an interesting molecular target for Luminal A breast cancer, especially associated with hormone therapy, aiming for adverse effect mitigation and higher therapeutic efficacy.